2016
DOI: 10.1002/chin.201622159
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Practical Synthesis of Phenanthridinones by Palladium‐Catalyzed One‐Pot C—C and C—N Coupling Reaction: Extending the Substrate Scope to o‐Chlorobenzamides.

Abstract: Scope to o-Chlorobenzamides. -(LIU, H.; HAN, W.; LI, C.; MA, Z.; LI, R.; ZHENG, X.; FU*, H.; CHEN, H.; Eur. J. Org. Chem. 2016, 2, 389-393, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…2-Bromobenzamides 7 could be subjected to Pd-catalyzed homocoupling, delivering phenanthridinone derivatives 8 [ 70 , 71 , 72 ] ( Scheme 4 ). In 2016, phenanthridinone synthesis was realized starting from o -halobenzamides under phosphine-free palladium catalysis in N , N -dimethylacetamide [ 73 ]. Authors also demonstrated this methodology in a scalable process by performing gram scale reactions.…”
Section: Simultaneous Aryl–aryl and N –Aryl Coupling Reactions For Phenanthridinone Synthesismentioning
confidence: 99%
“…2-Bromobenzamides 7 could be subjected to Pd-catalyzed homocoupling, delivering phenanthridinone derivatives 8 [ 70 , 71 , 72 ] ( Scheme 4 ). In 2016, phenanthridinone synthesis was realized starting from o -halobenzamides under phosphine-free palladium catalysis in N , N -dimethylacetamide [ 73 ]. Authors also demonstrated this methodology in a scalable process by performing gram scale reactions.…”
Section: Simultaneous Aryl–aryl and N –Aryl Coupling Reactions For Phenanthridinone Synthesismentioning
confidence: 99%